BIOCIDE SCREENING TEST TO PRODUCE WATER REINJECTION IN THE “X OIL FIELD” - Zulkifliani Zulkifliani (Testing Center for Oil and Gas LEMIGAS, 2017)
Oil field produced water with a high fl ow rate usually contains suspended solid, such as corrosion, scale, bacteria, clay, wax, and oil residue. Biocide is used to reduce viability of bacteria cell in produced water reused for produced water reinjection into oil reservoir. The objectives of this study is to examine anti bacteria activity of fi ve active compound biocides i.e. Glutaraldehide (Biocide-1), Aldehyde-Based and Surfactants (Biocide-2), Glutaraldehyde, Quartenary Ammonium Compounds (Biocide-3), Tetrakis Phosphonium Hydroxymethyl Sulfate (Biocide-4), and Amine Aldehide (Biocide-5) for reduced bacteria cell in produced water in this fi eld. Resulted in this study is general aerobic bacteria group is high contamination at the produced water reinjection. Bacteria isolates identifi ed is Bacillus sp (2 types of isolates) and Pseudomonas alcaligenes. The type of Biocides-2 and Biocide-3 reduced the number of bacteria cells maximal at a concentration of 200 ppm.Oil field produced water with a high fl ow rate usually contains suspended solid, such as corrosion,scale, bacteria, clay, wax, and oil residue. Biocide is used to reduce viability of bacteria cell in producedwater reused for produced water reinjection into oil reservoir. The objectives of this study is to examineanti bacteria activity of fi ve active compound biocides i.e. Glutaraldehide (Biocide-1), Aldehyde-Basedand Surfactants (Biocide-2), Glutaraldehyde, Quartenary Ammonium Compounds (Biocide-3), TetrakisPhosphonium Hydroxymethyl Sulfate (Biocide-4), and Amine Aldehide (Biocide-5) for reduced bacteriacell in produced water in this fi eld. Resulted in this study is general aerobic bacteria group is highcontamination at the produced water reinjection. Bacteria isolates identifi ed is Bacillus sp (2 types ofisolates) and Pseudomonas alcaligenes. The type of Biocides-2 and Biocide-3 reduced the number ofbacteria cells maximal at a concentration of 200 ppm.